The prestress-dependent mechanical response of magnetorheological elastomers. (23rd July 2015) - Feng, Jiabin; Xuan, Shouhu; Liu, Taixiang; Ge, Lin; Yan, Lixun; Zhou, Hong; Gong, Xinglong
Abstract: Magnetorheological elastomers (MREs) are intelligent materials consisting of a rubber matrix filled with magnetizable particles. In many engineering applications, MREs are usually pre-confined and work with constraint-induced prestress. The prestress can significantly change the mechanical properties of MREs. In this work, the influence of prestress on the mechanical response of MREs is studieds both experimentally and theoretically. The storage modulus as well as the magneto-induced modulus change non-linearly with increasing prestress and three regions can be found in the non-linear change. In the non-full contact region, the MREs present poor mechanical properties at small prestress due to the unevenness of the sample surface. In the full contact region, the MREs are under suitable prestress, thus they present good mechanical properties. In the overload region, the pre-configured microstructure of the MREs is destroyed under the large prestress. Moreover, an analytical model is proposed to study the prestress-dependent mechanical properties of MREs. It is revealed that the prestress can change the inter-particle distance, thus further affecting the mechanical response of MREs.